Thematic Roles Are Not Semantic Roles - van Voorst, Jan (Revue québécoise de linguistique, 1988)
AbstractThis article discusses the value of thematic roles for the description of phenomena of grammar. Notions like agent, patient, etc. do not have any explanatory value in the grammar. For instance, there is no relationship between the middle, subject selection in English and the impersonal passive in Dutch and these roles. This makes it impossible for the language learner to distil them from the grammatical system. The notion of Event Structure creates a more explanatory link between the grammar and semantics. This notion explains the functioning of impersonal passive in Dutch. It is notions like this one that should play a principal role in a more explanatory semantic theory.